Non-invasive assessment of pulmonary blood flow using an inert gas rebreathing device in fibrotic lung disease. Issue 4 (13th April 2010) - Corte, Tamera J; Wells, Athol U; Gatzoulis, Michael A; Cramer, Derek; Ward, Simon; Macdonald, Peter S; Dimopoulos, Konstantinos; Wort, Stephen J
Abstract : Background and aims: Pulmonary hypertension (PH) is increasingly recognised in patients with diffuse lung disease, and is associated with increased mortality. Cardiac output (CO) is a prognostic marker in PH. Non-invasive assessment of pulmonary blood flow (PBFINNOCOR ) with the inert gas rebreathing Innocor device has been validated against CO in PH, but not in PH associated with parenchymal lung disease. PBFINNOCOR may be less accurate in patients with lung disease because of intrapulmonary shunting and/or incomplete gas mixing. Our aim was to determine the variability of PBFINNOCOR in normal subjects, before evaluating PBFINNOCOR in diffuse lung disease against CO measured by the indirect Fick method (COFICK ) at right heart catheterisation (RHC). Methods and results: 23 normal subjects had lung volume measurements by a constant-volume body plethysmograph and three consecutive PBFINNOCOR measurements on the same day. 20 subjects returned for repeat assessment. PBFINNOCOR had good intrasession repeatability (coefficient of variation (CV)=6.57%) and intersession reproducibility (mean CO difference=0.13; single determinant SD=0.49; CV=9.7%). 28 consecutive patients with lung fibrosis referred for RHC had PBFINNOCOR measured within 24 h of RHC. There was good agreement between COFICK and PBFINNOCOR, with no evidence of systematic bias (mean COFICK 4.3±1.0; PBFINNOCOR 4.0±1.2l/ min; p=0.07). Bland–Altman analysis revealed a mean difference of −0.32 and limits of agreement of −2.10 to +1.45. Conclusion: Non-invasive PBF measured by the inert gas rebreathing Innocor device has good intrasession repeatability and intersession reproducibility. In diffuse lung disease, CO can be accurately and non-invasively measured by the Innocor device.